Boundaryless career and career success: the impact of emotional and social competencies - Gerli, Fabrizio; Bonesso, Sara; Pizzi, Claudio (Frontiers in Psychology, 2015)
Even though, over the last two decades, the boundaryless career concept has stimulated a wide theoretical debate, scholars have recently claimed that research on the competencies that are necessary for managing a cross-boundary career is still incomplete. Similarly, the literature on emotional and social competencies has demonstrated how they predict work performance across industries and jobs but has neglected their influence in explaining the individual’s mobility across boundaries and their impact on career success. This study aims to fill these gaps by examining the effects of emotional and social competencies on boundaryless career and on objective career success. By analyzing a sample of 142 managers over a period of eight years, we found evidence that emotional competencies positively influence the propensity of an individual to undertake physical career mobility and that career advancements are related to the possession of social competencies and depend on the adoption of boundaryless career paths. This study also provides a contribution in terms of the evaluation of the emotional and social competencies demonstrated by an individual and of the operationalization of the measurement of boundaryless career paths, considering three facets of the physical mobility construct (organizational, industrial and geographical boundaries).